Pain relief procedures before high-dose-rate brachytherapy for non-surgical treatment of cervix cancer - Pellizzon, Antonio Cássio Assis (Journal of Contemporary Brachytherapy, 2018)
Cervical cancer (CC) is a neoplasm with great potential for prevention, but it is still an important public health problem in most developing countries. No significant difference is found in the literature between intracavitary high-dose-rate (HDR) and low-dose-rate (LDR) brachytherapy, when considering overall, disease specific, and recurrence-free survivals. Cervical dilatation is mandatory for the insertion of intra-uterine tandems for CC intracavitary brachytherapy. Pain and discomfort may eventually be the limiting factors of the procedure, sometimes leading to unsatisfactory results in terms of adequate position of the applicator set. In this paper, we critically reviewed the current sedation and anesthetic options for comfort and safety procedures when performing intracavitary brachytherapy.